The Elementary Forms of Risk: The Mobility Immobilized / As Formas Elementares de Risco: A Mobilidade Imobilizada - Korstanje, Maximiliano E (Revista Rosa dos Ventos - Turismo e Hospitalidade, 2015)
Modernity and mobilities have been widely studied from many perspectives. Any movement opens new limens and boundaries that denote the status of travelers. In our days, neither the lineage nor the kinship determines the identity of subject. We often accept the belief that we live in a modern mobile world, which unlike ancient world, presents new opportunities to more free knowledge and social relations. But mobility engenders risks, and risk has been a buzz-word topic examined by sociology for more than 30 years. In contrast to current state of the art, that claims risks are negative elements that affect the advertising of tourist destinations, we argue that the risk is not only enrooted in capitalism, but also in the act of traveling. The concept of risk and mobilities are inextricably linked in the capitalist ethos. As Formas Elementares do Risco: A Mobilidade Imobilizada - <span style="font-size: 11.0pt; font-family: "Calibri","sans-serif"; mso-ascii-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: Arial; color: #222222; mso-ansi-language: PT;" lang="PT">Modernidade e<span style="font-size: 11.0pt; font-family: "Calibri","sans-serif"; mso-ascii-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: Arial; color: #222222; mso-ansi-language: PT;" lang="PT"> mobilidade tem sido amplamente estudadas por diferentes vieses acadêmicosnos, nos últimos 30 anos<span style="font-size: 11.0pt; font-family: "Calibri","sans-serif"; mso-ascii-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: Arial; color: #222222; mso-ansi-language: PT;" lang="PT">. Muito embora seja amplamente aceito que estejamos vivendo em um mundo móvel, se em comparação com outras civilizações, pouco se c<span style="font-size: 11.0pt; font-family: "Calibri","sans-serif"; mso-ascii-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: Arial; color: #222222; mso-ansi-language: PT;" lang="PT">onsidera-se que qualquer movimento ou deslocamento desafia a identidade e a pertença do sujeito ao território. A mobilidade, por sua vez, também gera riscos, levando a que o mesmo seja uma categoria de análise importante; em contraste com o que tem sido escrito, que postula risco como um aspecto negativo na propaganda de destinos turísticos, defende-se neste ensaio o risco como parte inerente da viagem e da mobilidade.